Prospects for sustainable resource-based development and diversification of the national economy - Alakbarov, S.; Алакбаров, С. Р. (Харківський національний автомобільно-дорожній університет, 2025)
This study examines the role of the oil and gas industry in ensuring economic stability in Azerbaijan and provides a comprehensive synthesis of theoretical and empirical approaches to sustainable economic development. The research employs comparative analysis, logical generalization, systematic approaches, and methods of analysis and synthesis to assess the impact of carbohydrates on macroeconomic stability, state budget revenues, and structural diversification. The study highlights that oil and gas revenues remain a central stabilizing factor in Azerbaijan‟s economy, contributing significantly to fiscal inflows, GDP growth, and intergenerational equity through institutional mechanisms such as the State Oil Fund of Azerbaijan (SOFAZ). Historical evidence, including the “Dutch disease” phenomenon, illustrates the risks of overreliance on carbohydrates and emphasizes the need for economic diversification and structural reforms. Empirical findings reveal that oil revenues account for approximately 46% of the state budget, while production trends indicate a gradual decline in oil output and moderate growth in natural gas production. The calculated economic diversification coefficient demonstrates that Azerbaijan‟s economy remains insufficiently diversified, around 40% below the optimal level, underlining the urgent need for policy measures that promote nonoil sectors, infrastructure development, and human capital accumulation. The study also considers global energy trends, the transition to renewable energy, and the integration of sustainability principles in line with international frameworks such as the UN Sustainable Development Goals (SDGs). The originality of the research lies in quantifying the depreciation coefficient of the economy, assessing the share of oil revenues in state budget revenues, and evaluating the macroeconomic impact of hydrocarbon dependency. The results provide practical implications for policymakers to strategically allocate oil revenues, strengthen institutional governance, and accelerate economic diversification to ensure long-term economic resilience. In conclusion, achieving sustainable economic development in Azerbaijan requires a balanced approach that integrates energy security, renewable energy adoption, structural transformation, and alignment with global sustainability objectives.
Перспективи сталого ресурсно-орієнтованого розвитку та диверсифікації національної економіки
Keywords: GDP; oil and gas production; economic diversification coefficient; state budget; multiplier; elasticity coefficient; nominal and real exchange rate; etc; ВВП; виробництво нафти та газу; коефіцієнт економічної диверсифікації; державний бюджет; мультиплікатор; коефіцієнт еластичності; номінальний та реальний обмінний курс тощо; 338.2:330.3; 10.30977/ЕТК.2225-2304.2025.46.215